Shop drawing of Hor. 'Z' louver at roof of change room (RFA-030_Rev-B) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.